2021
DOI: 10.1007/s11239-021-02509-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasmatic oxidative stress and thrombosis in primary antiphospholipid syndrome

Abstract: Antiphospholipid antibodies induce a pro-inflammatory and hypercoagulable state that lead to increased risk of thrombosis. Whether oxidative damage contributes thrombosis risk is a matter of debate. We evaluated the association between oxidative stress and thrombosis in primary antiphospholipid syndrome (t-PAPS). Plasma total antioxidant capacity and the levels of malondialdehyde (TBARs), carbonyl protein, and 8-isoprostane in plasma were determined in a group of patients with t-PAPS and in individuals without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
4
0
3
Order By: Relevance
“…However, IgG antibodies isolated from t-PAPS failed to reproduce the resistance to the inhibitory effect of SNP and iloprost and the reduction in cAMP or cGMP levels observed in PRP from t-PAPS patients. One possible explanation for this apparent discrepancy is that platelet and plasma from t-PAPS release proinflammatory, pro-coagulant, pro-oxidant mediators, 38,39 ectonucleotidases on the membrane surfaces from cells 40 that contribute to the exacerbation of the pathological responses induced by ADP and/ or by the reduction in the efficacy of substances that increase the levels of cAMP or cGMP.…”
Section: Discussionmentioning
confidence: 99%
“…However, IgG antibodies isolated from t-PAPS failed to reproduce the resistance to the inhibitory effect of SNP and iloprost and the reduction in cAMP or cGMP levels observed in PRP from t-PAPS patients. One possible explanation for this apparent discrepancy is that platelet and plasma from t-PAPS release proinflammatory, pro-coagulant, pro-oxidant mediators, 38,39 ectonucleotidases on the membrane surfaces from cells 40 that contribute to the exacerbation of the pathological responses induced by ADP and/ or by the reduction in the efficacy of substances that increase the levels of cAMP or cGMP.…”
Section: Discussionmentioning
confidence: 99%
“… 82 However, in the study by Vaz et al no differences were found between thrombotic PAPS patients (n = 70) and controls (n = 74) when comparing total antioxidant capacity, oxidative damage and oxidative balance measured by the concentration of protein carbonyl and 8-isoprostane. 83 We highlight that the aforementioned studies 81 , 82 did not include a homogeneous group of PAPS patients as was done in the study by Vaz et al 83 The study by Sciascia et al 81 classified the APS patients (n = 45) as PAPS or APS associated with other immunological diseases, and the study by Perez-Sanchez et al 82 enrolled 25 APS patients with thrombotic manifestation and 19 with pregnancy morbidity. In addition, the different thrombotic treatments in patients may explain the discrepancies between studies.…”
Section: Pathogenetic Mechanisms In Apsmentioning
confidence: 99%
“…Антифосфоліпідний синдром (АФС)це автоімунний процес, який характеризується венозним та артеріальним тромбозом, невиношуванням вагітності з постійною циркуляцією антифосфоліпідних антитіл (АФА). У патогенезі АФС важливу роль відіграють вовчаковий антикоагулянт та антитіла до β-2-глікопротеїну І [1][2][3]. Раніше вважали, що АФА зв'язуються з кардіоліпіном, проте зараз відомо, що вони спрямовані проти протеїнів, зчеплених із фосфоліпідами у клітинній мембрані.…”
unclassified
“…Раніше вважали, що АФА зв'язуються з кардіоліпіном, проте зараз відомо, що вони спрямовані проти протеїнів, зчеплених із фосфоліпідами у клітинній мембрані. Основним антигеном вважають β-2-глікопротеїн І, проте він не є тромбогенним, тому механізми виникнення тромбозу і втрати вагітності при АФС залишаються до кінця не вивченими [2,4]. За даними літератури, до головних механізмів розвитку тромбозів при АФС належать активація судинних клітин, інгібування природних систем фібринолізу та антикоагуляції і прокоагулянтний вплив позаклітинних везикул.…”
unclassified
See 1 more Smart Citation